1996
DOI: 10.1139/l96-047
|View full text |Cite
|
Sign up to set email alerts
|

Design rated oriented strandboard in CSA standards

Abstract: The 1994 edition of CSA (Canadian Standards Association) Standard 086.1 "Engineering design in wood" includes, for the first time, specified strength and stiffness for design rated oriented strandboard (OSB). Design rated OSB panels are manufactured in accordance with the new CSA Standard 0452. In this paper, the results of the short-term (1–10 min) test data which led to the establishment of the three rating grades of Type 1 (standard) design rated OSB are presented. In addition, factors that may affect the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 2 publications
5
13
0
Order By: Relevance
“…However, the average values of planar shear modulus of rigidity in the major and minor axes, Gxz and Gyz, respectively, for the OSB test panel (51 -72 N/mm 2) are low compared to other published values of Gxz and G yz that are typically in the range from 150 to 200 N/ram [4,6]. The relatively low shear stiffnesses from the bending and shear tests are related to the density distribution through the thickness, the relative layer thickness, resin distribution and degree of strand orientation in the test board.…”
Section: Discusssionmentioning
confidence: 68%
See 3 more Smart Citations
“…However, the average values of planar shear modulus of rigidity in the major and minor axes, Gxz and Gyz, respectively, for the OSB test panel (51 -72 N/mm 2) are low compared to other published values of Gxz and G yz that are typically in the range from 150 to 200 N/ram [4,6]. The relatively low shear stiffnesses from the bending and shear tests are related to the density distribution through the thickness, the relative layer thickness, resin distribution and degree of strand orientation in the test board.…”
Section: Discusssionmentioning
confidence: 68%
“…Numerous studies of solid wood have shown that there is strong correlation between the bending modulus of elasticity and planar shear modulus of rigidity [9]. In the case of OSB, such a correlation has so far not been shown [6,7]. However, if there is a correlation, linear or non-linear, between the planar shear modulus of rigidity and the planar shear strength, the planar shear modulus of rigidity determined from bending test can roughly give an indication of the planar shear strength.…”
Section: Evaluation and Significancementioning
confidence: 99%
See 2 more Smart Citations
“…The test results reveal that the ratio of major to minor axes of the failed envelope is about 1.3, and is of the same order as the levels of orthotropy in planar shear rather than the levels of orthotropy in bending MOE and strength of 2.7 and 1.7 respectively. The values of the planar shear properties of other OSB [9,10] show that the levels oforthotropy in planar shear strengths and MOEs range typically from 0.7 to 1.3. Assuming that the ratio of major to minor axes of the failed elliptical envelope is of the same order as the level of orthotropy in planar shear, then the shape or eccentricity of the elliptical failure envelope for other types of OSB panels can be predicted.…”
Section: Discussionmentioning
confidence: 99%